Evaluation of the Roche Neisseria gonorrhoeae 16S rRNA PCR for Confirmation of AMPLICOR PCR-Positive Samples and Comparison of Its Diagnostic Performance According to Storage Conditions and Preparation of Endocervical Specimens - Van Dyck, E. (American Society for Microbiology, 2001)
The AMPLICOR PCR was used to detect Neisseria gonorrhoeae in endocervical specimens. A 16S rRNA PCR performed on N. gonorrhoeae-positive samples showed sensitivities of 73.2, 64.3, and 94.4% for samples treated directly with AMPLICOR lysis buffer, samples suspended in 2-sucrose phosphate, and samples suspended in diluted phosphate-buffered saline, respectively.